2002
DOI: 10.1046/j.1360-0443.2002.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in help‐utilization and the 8‐year course of alcohol abuse

Abstract: The results suggest that although alcoholism interventions were designed primarily for men, they are currently delivered in ways that are also useful to women. Problem-drinking women appear to benefit from sustained participation in AA, which emphasizes bonding with supportive peers to maintain abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
36
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 50 publications
(56 reference statements)
9
36
0
2
Order By: Relevance
“…Despite women's shorter interval between regular drug use and treatment entry Hernandez-Avila et al, 2004;McCance et al, 1999), however, several studies in clinical populations have found little difference in the likelihood or rate of treatment entry between women and men (Green et al, 2002;Timko et al, 2002). There are only a few studies that have directly examined gender differences in the likelihood of substance abuse treatment entry.…”
Section: Gender Disparities In Treatment Entry and Ever Receiving Trementioning
confidence: 99%
See 1 more Smart Citation
“…Despite women's shorter interval between regular drug use and treatment entry Hernandez-Avila et al, 2004;McCance et al, 1999), however, several studies in clinical populations have found little difference in the likelihood or rate of treatment entry between women and men (Green et al, 2002;Timko et al, 2002). There are only a few studies that have directly examined gender differences in the likelihood of substance abuse treatment entry.…”
Section: Gender Disparities In Treatment Entry and Ever Receiving Trementioning
confidence: 99%
“…A secondary analysis of data from the prospective U.S. National Treatment Improvement Evaluation Study including 1,123 women and 2,019 men in 59 treatment facilities (Marsh et al, 2004) found that receipt of comprehensive services, including educational, housing, and income support, were related to post-treatment outcomes for both men and women. When gender differences have been found, adult women generally have had better outcomes than men, despite differences in populations targeted, type of treatment, problem drug, and treatment setting (de Leon and Jainchill, 1981;Hser et al, 2005;Fiorentine et al, 1997;Jarvis., 1992;Kosten et al, 1993;Kranzler et al, 1996;McKay et al, 2003;Nurco et al, 1988;Project MATCH, 1997;Rivers et al, 2001;Sanchez-Craig et al, 1991;Satre et al, 2004;Stephens et al, 1994;Timko et al, 2002). For example, while women had more severe family and social problems at treatment entry in a study of cocaine-dependent individuals admitted to an inpatient treatment program , there were no gender differences in family and social problems at follow-up, and women were more likely than men to have remained abstinent at six-month follow-up.…”
Section: Substance Abuse Outcomes Versus Predictors Of Outcomesmentioning
confidence: 99%
“…Ainda que diferentes estudos não tenham conseguido chegar a conclusões consistentes e definitivas, características já associadas à adesão ao tratamento de alcoolistas incluem: o envolvimento de familiares ou pessoa próxima e significativa 4 ; ordenação judicial 5 ; gênero 6 ; idade 7 ; uso de outras substâncias psicoativas e psicopatologia comórbida 8,9 ; intensidade e duração do tratamento 10,11 . Aparentemente, descrença na gravidade clínica das conseqüências do uso de álcool pode resultar a falta de adesão ao tratamento 12 .…”
Section: Artigo Originalunclassified
“…Efetivamente, tratamento prévio 23 , maior número de internações para desintoxicação 6 , assim como maior freqüência ao AA 6,24 já foram identificados como preditores de bons resultados de tratamento. Por outro lado, pode-se supor que internações decorrentes de episódios de irritabilidade teriam sido buscadas por terceiros -em circunstâncias de ausência de autocrítica; a consciência da própria irritabilidade sob efeito do álcool -conforme referido anteriormente, na abordagem de sentimentos -resultaria mais alto nível de insight e, por conseguinte, de adesão ao tratamento.…”
Section: Tratamento Anterior Ou Atualunclassified
“…Alcoholism treatment programmes are also economically efficient if the patient remained sober up to 12 months (7,8). On the other hand, to the best of our knowledge, few studies researched prognostic factors for stabile abstinence and long-term benefits (more than five years) of treatment due to complexity of factors influencing the outcomes (9)(10)(11), or the studies used very specific populations (e.g. adolescents, young adults, specific co-morbid conditions) (e.g.…”
Section: Introductionmentioning
confidence: 99%